Intonation role in communication with the child (Eurasian Journal of Philology Science and Education, 2018)
This article is devoted the intonation role in communication with the childюDevelopment of the speech of children of preschool age by means of intonation are closely connected with features of development of thinking, psychological state of the child. The children’s preschool age is one of the most important stages of development of his lexicon. At this time the child begins to study language units from separate words to phrases. At the same time the intonation as nonverbal means of language influences development of oral speech of children. Moreover it is impossible to deny that here a major factor is the social circle of the child. The result of social interaction of the child with others is reflected in his language. The speech of the child also begins with intonation. During the before verbal period which is considered preparatory to speech activity for the child initially the floor isn’t given to the semantic importance, and the carrier of «sense» is the intonation, speed, a voice timbre, a melodics.Results of a research show that intonational features of the speech of parents exert a great influence on intonational aspect of children’s language and play an important role in ability to communicate with other people and to control the emotions.